Transmitted drug resistance in recently infected HIV-positive Individuals from four urban locations across Asia (2007-2010) - TASER-S - Awachana Jiamsakul (2018)
© Jiamsakul et al. Background: The availability of HIV antiretroviral therapy (ART) has been associated with the development of transmitted drug resistance-associated mutations (TDRM). TDRM can compromise treatment effectiveness in patients initiating ART and the prevalence can vary in different clinical settings. In this study, we investigated the proportion of TDRM in treatment-naïve, recently infected HIV-positive individuals sampled from four urban locations across Asia between 2007-2010. Methods: Patients enrolled in the TREAT Asia Studies to Evaluate Resistance - Surveillance Study (TASER-S) were genotyped prior to ART initiation, with resulting resistance mutations analysed according to the WHO 2009 list. Results: Proportions of TDRM from recently infected individuals from TASER-S ranged from 0% to 8.7% - Hong Kong: 3/88 (3.4%, 95% CI (0.71%-9.64%)); Thailand: Bangkok: 13/277 (4.7%, 95% CI (2.5%-7.9%)), Chiang Mai: 0/17 (0%, 97.5% CI (0%-19.5%)); and the Philippines: 6/69 (8.7%, 95% CI (3.3%-18.0%)). There was no significant increase in TDRM over time across all four clinical settings. Conclusions: The observed proportion of TDRM in TASER-S patients from Hong Kong, Thailand and the Philippines was low to moderate during the study period. Regular monitoring of TDRM should be encouraged, especially with the scale-up of ART at higher CD4 levels.